In Silico Molecular Docking, Synthesis and Preliminary Evaluation of Antibacterial Activity of Levofloxacin Carboxamides with Certain Amino Acids - Sarah Abdul-Razzaq makki; Shakir M Alwan; Mayada H. Al-Qaissy (Al-Mustansiriyah Journal of Pharmaceutical Sciences, 2023)
Levofloxacin carboxamides with certain amino acids were prepared through an amide linkage to the amino acid (glycine, histidine, or serine). These carboxamides were subjected to an in silico molecular docking evaluation on